2013
DOI: 10.1159/000356313
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Rockall Scoring System in Predicting the Need for Intervention and Outcomes in Patients with Nonvariceal Upper Gastrointestinal Bleeding in a Brazilian Setting: A Prospective Study

Abstract: Background/Aims: This prospective study investigated the performance of pre-endoscopy and the complete Rockall scores in predicting the occurrence of adverse outcomes and the need for endoscopic or surgical intervention in patients with nonvariceal upper gastrointestinal bleeding. Methods: All 656 consecutive patients who underwent endoscopy due to nonvariceal upper gastrointestinal bleeding between 2007 and 2011 were included. Receiver operating characteristic (ROC) curves were plotted for the outcomes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…CRS was reported to have an acceptable performance in predicting mortality. 19 Similar to our results, Cassana A et al 20 reported that GBS has no diagnostic validity in predicting mortality in UGIB. Wang CH et al 2 found that GBS, CRS, and PRS have no good performance in predicting 30-day mortality in UGIB.…”
Section: Discussionsupporting
confidence: 89%
“…CRS was reported to have an acceptable performance in predicting mortality. 19 Similar to our results, Cassana A et al 20 reported that GBS has no diagnostic validity in predicting mortality in UGIB. Wang CH et al 2 found that GBS, CRS, and PRS have no good performance in predicting 30-day mortality in UGIB.…”
Section: Discussionsupporting
confidence: 89%
“…While some authors suggested that the PreRS was not useful in predicting death when compared to the PostRS [14], others presented results admitting that the PreRS can be as good as the PostRS in predicting mortality [15, 16]. In our cohort of patients, the PreRS and PostRS were the only scores which could accurately predict 30-day mortality, exhibiting similar performances.…”
Section: Discussionmentioning
confidence: 61%
“…Concerning mortality, area under the receiver operating characteristic curve (AUROC) of GBS and RS is reported to range from 0.65 to 0.90 and from 0.64 to 0.85, respectively . Concerning the necessity for transfusion, the AUROC of GBS and RS ranged from 0.81 to 0.94 and from 0.70 to 0.79, respectively .…”
Section: Initial Management Of Non‐variceal Upper Gastrointestinal Blmentioning
confidence: 99%
“…Concerning the necessity for transfusion, the AUROC of GBS and RS ranged from 0.81 to 0.94 and from 0.70 to 0.79, respectively . Concerning the necessity for endoscopic hemostasis, the AUROC of GBS and RS ranged from 0.604 to 0.960 and from 0.653 to 0.822, respectively . Both GBS and RS are useful to identify low‐risk cases.…”
Section: Initial Management Of Non‐variceal Upper Gastrointestinal Blmentioning
confidence: 99%